Enantioselective Catalytic Aldol Reactions in the Presence of Knoevenagel Nucleophiles: A Chemoselective Switch Optimized in Deep Eutectic Solvents Using Mechanochemistry - Hanaa Al Beiruty; Sofiia-Stefaniia Zhylinska; Nino Kutateladze; Hayley Kay Tinn Cheong; José A. Ñíguez; Sarah J. Burlingham; Xavier Marset; Gabriela Guillena; Rafael Chinchilla; Diego A. Alonso; Thomas C. Nugent (Molecules, 2023)
In the presence of different nucleophilic Knoevenagel competitors, cyclic and acyclic ketones have been shown to undergo highly chemoselective aldol reactions with aldehydes. In doing so, the substrate breadth for this emerging methodology has been significantly broadened. The method is also no longer beholden to proline-based catalyst templates, e.g., commercially available O-t-Bu-L-threonine is advantageous for acyclic ketones. The key insight was to exploit water-based mediums under conventional (in-water) and non-conventional (deep eutectic solvents) conditions. With few exceptions, high aldol-to-Knoevenagel chemoselectivity (>10:1) and good product profiles (yield, dr, and ee) were observed, but only in DESs (deep eutectic solvents) in conjunction with ball milling did short reaction times occur.